In vitro evaluation of concentration, labeling effectiveness and stability for 131I‐labeled radioimmunoassay ligand using real‐time detection technology. (13th December 2016) - Barta, Pavel; Janousek, Jiri; Zilkova, Katerina; Trejtnar, Frantisek
Abstract : Radioimmunoassay belongs to the analytical method enabling highly specific and sensitive quantification of molecules. The verification of the real‐time radioimmunoassay technology usefulness for ligand‐quality characteristics evaluation such as concentration, influence of radiolabeling on binding affinity and stability was estimated. The anti‐epidermal growth factor receptor antibody 131 I‐cetuximab was employed as the ligand antibody. The concentration of 131 I‐cetuximab was derived from the shape of binding curves coming from the ligand‐receptor interaction. The binding curves also allowed the estimation of 131 I‐cetuximab binding affinity for different radiolabeling procedures (incubation times 1, 5, and 10 minutes) in stability testing up to 96 hours at 4°C. The stability testing also included comparative analysis by size exclusion high‐performance liquid chromatography. The assessment of cetuximab concentrations using real‐time method showed acceptable accordance between real and calculated values. The real‐time method revealed that 1‐minute radiolabeling proved to be the optimal incubation time for direct radioiodination of cetuximab. Stability testing showed the significant change in radioligand affinity by one order at the longest incubation times (72 and 96 hours). Characterization of stability and binding behavior of radiolabeled monoclonal antibodies by the verified real‐time method before use in other assays may be employed to eliminate variability and suboptimal antibody performance. Abstract : Highlights Specific concentration curve shape rendered the information for concentration determination. Real‐time radioimmunoassay successfully characterized important parameters of 131 I‐ligand. 131 I‐cetuximab binding affinity significantly changed for the long radioiodination times. The quality of ligand‐receptor interaction was changed with elapsed shelf life.